Features and Applications of Urine Stabilization Methods: A Review - Yang, Wei; Li, Jianan; Yang, Xuejing (Frontiers in Sustainability, 2021)
The recovery of nutrients from unconventional water such as domestic sewage is considered as a sustainable solution to environmental sanitation, personal hygiene, water and food safety issues. Source separation of urine and the sequenced treatment techniques are the promising approaches to recover the resources from this unconventional water. However, in the storage of urine, urea is hydrolyzed under the action of urease, resulting in peculiar smell, precipitation and the loss of ammonia, which is a challenge to be overcome in the process of urine recycling. This review collates research related to urine stabilization, and aims to summarize the characteristics and applications of existing urine stabilization methods, such as acidification, alkalization, electrochemistry, inhibitors and etc. Overall, acidification and alkalization require precise dosage and have an attentional impact on the environment; electrochemical technology is suitable for decentralized sanitation facilities, but the inhibition duration is short; inhibitors are the least effective and are usually used to regulate urease activities in soil environment rather than for urine stabilization. Choosing the appropriate approaches of urine stabilization should focus on the overall perspective of urine resource utilization, consider the separation method and recovery form, and combine it with the concentration technology.